Prática supervisionada de exercícios físicos durante o tratamento regular com estatinas de pacientes da atenção básica: caracterização, aderência e delimitação das respostas musculares - Bonfim, Mariana Rotta [UNESP] (2015)
In the Brazilian public health context, little is known about the particularities of statin treatment, and the mechanisms implied in skeletal muscle effects due to the association of long-term treatment and moderate physical activity. Thus, the aims of this study were to evaluate the actions for statin treatment in primary care, so as to assess muscle skeletal effects of statin treatment alone and in association with a moderate physical activity program developed in basic healthcare units. So, information collection in clinical reports was conduct in order to obtain health state and medication treatments of female patients (n=62) assisted in a basic healthcare unit (BHU). Identified patients were evaluated for socioeconomic state, comorbidities, medications in use, physical activity practice, self-reported muscle pain, adherence to medication treatment and body composition (n=72). In the following steps, only sedentary and menopause patients were included (n=61); of them, a sample was submitted to muscle biopsies (n=21) and test of muscle fucntion (n=17). For sedentary state (n=12) or aerobic (50 minutes) and resistance (25 minutes) physical exercise practice (n=13), three times per week, during 20 weeks, only free-statin predisposing muscle injury factors patients were included. In the end of intervention period, all parameters were revaluated. Medical attitude of modifying statin doses (48.4%) and/or types (25.4%) aimed lipid profile adequacy without muscle injuries. The frequency of non-adherent patients were 15.5% and mainly occurred in younger females (p=0.057), with less morbidities (p=0.011) and medication consumption (p=0.001). Muscle biopsies indicated patterns of metabolic (MET) and neurogenic (NEU) injuries, that occurred alone or associated, and had influenced the time to reach peak force (NEU > MET+NEU, p=0.01) and the percentage of force loss (NEU < MET+NEU, p=0.01). Adding moderate physical exercise to regular treatment ...